2019
DOI: 10.1002/app.48759
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of circumferentially aligned polymer nanofibers floating on rotating water collector

Abstract: This work outlines a novel electrospinning process using a rotating water collector. The circumferentially aligned nanofibers are successfully fabricated using this process. The movement and conductivity of the liquid collector are considered as the two prime factors to investigate the interaction between electrospun nanofibers and liquid surface. Through the theoretical analysis of the movement of liquid collector, it is confirmed that the liquid flow velocity demonstrates a tendency to decline from the cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Our previous research has shown that the flow velocity of the liquid vortex decreases from the vortex center 20 . Furthermore, it was found that the tangential velocity can be used to express the total velocity because of its large order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research has shown that the flow velocity of the liquid vortex decreases from the vortex center 20 . Furthermore, it was found that the tangential velocity can be used to express the total velocity because of its large order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…It can easily produce standalone fibers because of the easy separation between the fiber and the liquid surface. Additionally, the use of liquid collectors in electrospinning can also produce fibers more effectively with diverse morphologies, such as fiber yarns 19 and circumferentially aligned fibers 20 . Although liquid collectors have several merits over solid collectors, the former have not attracted much attention in previous studies because they exhibit a relatively weaker electrical conductivity than the typical solid collector, making it difficult to quickly transfer the charges carried by the deposited fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic charge is applied to the polymer in liquid form, which is extruded through a small jet, resulting in the nanofibers which are deposited on the metallic collector [ 113 ]. Conventional electrospun fibers can be aligned randomly or in the vertically aligned fashion, creating a tightly packed, 2D mesh which is similar to native ECM of some tissues, e.g., skin [ 114 ]. However, as was noted before, the cartilage and bone are complex hierarchical structures.…”
Section: Methods Of Scaffold Fabricationmentioning
confidence: 99%
“…Then, a continuous bundle composed of loosely aligned nanofibers was taken on a rotating roller and it was possible to collect continuously and without interruption for hours. In addition to insulating liquids, conductive liquids, such as an electrolyte solution, have been used as collectors 121 . For example, using an electrolyte solution, the nanofiber deposit can be controlled by changing the salt concentration and creating a nanofiber deposit on the surface of the conductive liquid electrolyte solution 122 …”
Section: Electrospinning With Liquid Bath Collectormentioning
confidence: 99%